Effects of human disturbance on nest placement of the woodpigeon (Columba palumbus): a case study from the Middle Atlas, Morocco. (Integrative zoology, 2014)
The woodpigeon (Columba palumbus) is a common and widespread bird in Morocco (North Africa). I examined, over 2 years (2010 and 2011), the breeding density and nest placement of this game species in relation to nest site habitat and degree of human disturbance. The study area was in the Middle Atlas Tighboula mountain forest, Morocco, in a disturbed and an undisturbed site. Using data collected in the 2 study sites, I aimed to identify the factors influencing the placement of nests within holm oak trees (Quercus rotundifolia) and their densities. I found that habitat structures, influenced by grazing disturbance, have affected nesting density and the location of nests of this species. Woodpigeons place their nests in a higher position (3.42 ± 0.19 m) when disturbance intensity is high and lower (1.68 ± 0.1 m) when disturbance intensity is low, and show higher nesting density in less disturbed zone (3.1 ± 0.4 nests/ha) than in highly disturbed zones (1.4 ± 0.2 nests/ha). Grazing disturbance could pose a threat to population persistence at a broader scale and could potentially reduce the abundance of this species by altering the composition and the structure of the forest nesting habitat. Further multi-scale studies are needed to assess the effects of different levels of grazing disturbance on woodpigeon nest density and placement, and to enhance our knowledge of the breeding behavior of this game species under variable environments.